Case report: Laparoscopic nissen-sleeve gastrectomy in a young adult with incidental finding of Morgagni-Larrey hernia - Palma, Rossella; Angrisani, Francesco; Santonicola, Antonella; Iovino, Paola; Ormando, Vittorio Maria; Maselli, Roberta; Angrisani, Luigi (Frontiers in Surgery, 2023)
Laparoscopic sleeve Gastrectomy (LSG) is the most performed bariatric procedure worldwide but it is associated with an increased incidence of de-novo or recurrent GERD. Recently a new technique consisting in LSG with associated fundoplication has been described.Morgagni-Larrey hernia is very rare and there is a lack of evidences on its correct surgical treatment.There are only rare cases of a MLH incidental diagnosis in patients submitted to bariatric surgery.We present our experience of Morgagni-Larrey Hernia (MLH) incidentally found intraoperatively in a patient with Gastroesophageal Reflux Disease (GERD) with Hiatal Hernia (HH) undergoing a bariatric surgical procedure.